Temperature sensitivity of Bragg gratings in PMMA and TOPAS microstructured polymer optical fibres - Webb, David J.; Kalli, Kyriacos; Zhang, Chi; Komodromos, Michael; Argyros, Alexander; Large, Maryanne C J; Emiliyanov, Grigoriy; Bang, Ole; Kjær, Erik Michael (My University, 2008)
We report on the temperature response of FBGs recorded in pure PMMA and TOPAS holey fibres. The gratings are fabricated for operational use at near IR wavelengths, using a phase mask and a CW He-Cd laser operating at 325nm. The room temperature grating response is non-linear and characterized by quadratic behaviour for temperatures from room temperature to the glass transition temperature, and this permanent change is affected by the thermal history of the gratings. We also report the first FBG inscription in microstructured polymer optical fibres fabricated from TOPAS. This material is fully polymerized and has very low moisture absorption, leading to very good fibre drawing properties. Furthermore, although TOPAS is chemically inert and bio-molecules do not readily bind to its surface, treatment with Antraquinon and subsequent UV activation allows sensing molecules to be deposited in well defined spatial locations. When combined with grating technology this provides considerable potential for label-free bio-sensing.
Keywords: Bio-sensing; Fibre Bragg gratings; PMMA; Polymer optical fibre; Temperature response; TOPAS